2021
DOI: 10.3389/fcell.2021.561086
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive miRNome-Wide Profiling in a Neuronal Cell Model of Synucleinopathy Implies Involvement of Cell Cycle Genes

Abstract: Growing evidence suggests that epigenetic mechanisms like microRNA-mediated transcriptional regulation contribute to the pathogenesis of parkinsonism. In order to study the influence of microRNAs (miRNAs), we analyzed the miRNome 2 days prior to major cell death in α-synuclein-overexpressing Lund human mesencephalic neurons, a well-established cell model of Parkinson’s disease (PD), by next-generation sequencing. The expression levels of 23 miRNAs were significantly altered in α-synuclein-overexpressing cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…Recently, some cell cycle genes were found enriched in a cell model of PD, and CCND1 was reported as upregulated and involved in alpha-synuclein cell death. It was shown that the knockdown of CCND1 reduces cell death [43], reinforcing our results of upregulation of miRNAs that regulate CCND1 in the brain.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, some cell cycle genes were found enriched in a cell model of PD, and CCND1 was reported as upregulated and involved in alpha-synuclein cell death. It was shown that the knockdown of CCND1 reduces cell death [43], reinforcing our results of upregulation of miRNAs that regulate CCND1 in the brain.…”
Section: Discussionsupporting
confidence: 88%
“…As documented for epileptic seizures, such alterations of neuronal activity may promote adult neurogenesis ( Jessberger and Parent, 2015 ). Finally, α-syn pathology through gain or loss of function may directly impact mechanisms of cell cycle regulation along the process of neurogenesis, leading to NPCs stuck or shifting in proliferation or maturation processes ( Lee et al, 2003 ; Winner et al, 2012 ; Rodríguez-Losada et al, 2020 ; Findeiss et al, 2021 ). If α-syn pathology spreads across synapses ( Chu and Kordower, 2015 ; Melki, 2018 ), none of the above mechanisms require a direct intracellular toxicity in DG neurons, which could be argued against given the relatively low expression level of α-syn in this region, physiologically and in Thy1-aSyn mice as discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Hsa-miR-34a-5p was the most signi cantly upregulated miRNA in our study. Hsa-miR-34a-5p has been reported to be expressed in blood mononuclear cells [40], neurons [41], T cells [42], and several cancer cell lines [43]. It has been shown to regulate T-cell differentiation and plasticity by targeting histone gene expression and histone modi cation [42] to play a critical role as a tumor suppressor via regulation of the p53 signaling pathway to mediate cell proliferation, invasion, and apoptosis [44] and to be implicated in large B-cell lymphoma [44] and lung broblasts [45].…”
Section: Discussionmentioning
confidence: 99%